2022
DOI: 10.3390/met13010003
|View full text |Cite
|
Sign up to set email alerts
|

Study on Friction and Wear Properties and Mechanism at Different Temperatures of Friction Stir Lap Welding Joint of SiCp/ZL101 and ZL101

Abstract: In order to achieve the goal of lightening the braking system of urban rail trains, SiCp/ZL101 and ZL101 plates were welded by friction stir lap welding (FSLW) to prepare a new type of brake disc material. The friction and wear properties of the friction-stir-processed composite material were studied at different temperatures (30 °C, 100 °C, 150 °C, 200 °C, 250 °C, 300 °C) to provide a theoretical basis for the evaluation of braking performance. The experimental results showed that the sliding friction process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Yuan et al [7] studied the friction and wear properties of friction stir welding CiCp/ZL101 and Zl101 composites at different temperatures. The results showed that the sliding friction process at each temperature was relatively stable, and the average friction coefficient was stable at about 0.4.…”
Section: Contributionsmentioning
confidence: 99%
“…Yuan et al [7] studied the friction and wear properties of friction stir welding CiCp/ZL101 and Zl101 composites at different temperatures. The results showed that the sliding friction process at each temperature was relatively stable, and the average friction coefficient was stable at about 0.4.…”
Section: Contributionsmentioning
confidence: 99%